Characterization of the promoter region of the mouse Xist gene. - Pillet, N (1995)
The mouse Xist gene is expressed exclusively from the inactive X chromosome and may be implicated in initiating X inactivation. To better understand the mechanisms underlying the control of Xist expression, we investigated the upstream regulatory region of the mouse Xist promoter. A 1.2-kb upstream region of the Xist gene was sequenced and promoter activity was studied by chloramphenicol acetyltransferase (CAT) assays after transfection in murine XX and XY cell lines. The region analyzed (-1157 to +917 showed no in vitro sex-specific promoter activity. However, a minimal constitutional promoter was assigned to a region from -81 to +1, and a cis element from -41 to -15 regulates promoter activity. We showed that a nuclear factor binds to an element located at -30 to -25 (TTAAAG). A second sequence at -41 to -15 does not act as an enhancer and is unable to confer transcriptional activity to the Xist gene on its own. A third region from -82 to -41 is needed for correct expression. Deletion of the segment -441 to -231 is associated with an increase in CAT activity and may represent a silencer element.